EFEKTIVITAS MODEL PEMBERDAYAAN DIRI TERHADAP AKTIVITAS PERAWATAN DIRI KLIEN DIABETES MELITUS TIPE 2 - Febrina Angraini Simamora; Hotma Royani Siregar (Jurnal Education and Development, 2019)
The increase in type 2 diabetes mellitus sufferers in the world requires that sufferers must be able to empower themselves to be able to prevent complications, disabilities, and dependence in conducting self-care. An intervention strategy that allows clients to make decisions about goals, therapeutic choices, and self-care behaviors and to assume responsibility for effective daily diabetes care in helping clients care for themselves. This study aims to determine the effectiveness of self-empowerment in self-care activities of type 2 diabetes mellitus clients. The study design used was a quasy experiment with a one group pretests-posttest only design. The sampling technique used was consecutive sampling with a sample of 16 people based on the power analysis table. The measuring instrument used was SDSCA (summary diabetes self care activities). Data analysis used paired t-test with p value 0.0001 (p value <0.05) which showed that the model of self empowerment was effective in increasing self-care activities of type 2 diabetes mellitus clients. Patients with type 2 diabetes mellitus were expected to be able to regulate their diet, physical exercise, and routine control of blood sugar levels.